Flouting Maxim in Chris Watts’s Interrogation: Pragmatics Study - Ervina CM Simatupang; Vannya Choirunnisa (International Journal of English Linguistics, Literature, and Education (IJELLE), 2023)
This research aims at analyzing the flouting of maxims and the reasons for flouting maxims that were committed by Chris Watts during his interrogation. This research used a descriptive qualitative method as a research design and a video entitled "FBI Interrogation of Chris Watts (BEST AUDIO)" on the "True Psych Ward" YouTube channel as data. The instrument of this research was the transcript text of the utterances between the interrogator and Chris Watts, consisting of flouting maxims. The researcher then found twenty-five (25) data containing all the types of flouting maxims due to Grice's theory, the Cooperative Principles, which consist of flouting maxim quality, quantity, relevance, and manner. On one hand, the result showed that there are 8 utterances containing flouting maxim of quality (32%), 6 flouting maxim of quantity (24%), 8 flouting maxim of relevance (32%), and 3 maxim of manner (12%). After analyzing the findings, the most dominant types were flouting maxim of quality and relevance, which means that Chris frequently gives information that is not in accordance with facts and data, and often says something that is not relevant or related to the topic being discussed. On the other hand, there are some reasons that appeared to be Chris Watts’s reason to flout the maxims, which are 10 data of hiding the truth (40%), 6 data of saving face (24%), 4 data of building one’s believe (16%), 3 data of satisfying the hearer (12%), and 2 data of convincing the hearer (8%).